Towards the development of a sustainable soya bean‐based feedstock for aquaculture. Issue 2 (13th September 2016) - Park, Hyunwoo; Weier, Steven; Razvi, Fareha; Peña, Pamela A.; Sims, Neil A.; Lowell, Jennica; Hungate, Cory; Kissinger, Karma; Key, Gavin; Fraser, Paul; Napier, Johnathan A.; Cahoon, Edgar B.; et al.
Summary: Soya bean ( Glycine max (L.) Merr.) is sought after for both its oil and protein components. Genetic approaches to add value to either component are ongoing efforts in soya bean breeding and molecular biology programmes. The former is the primary vegetable oil consumed in the world. Hence, its primary usage is in direct human consumption. As a means to increase its utility in feed applications, thereby expanding the market of soya bean coproducts, we investigated the simultaneous displacement of marine ingredients in aquafeeds with soya bean‐based protein and a high Omega‐3 fatty acid soya bean oil, enriched with alpha‐linolenic and stearidonic acids, in both steelhead trout ( Oncorhynchus mykiss ) and Kampachi ( Seriola rivoliana ). Communicated herein are aquafeed formulations with major reduction in marine ingredients that translates to more total Omega‐3 fatty acids in harvested flesh. Building off of these findings, subsequent efforts were directed towards a genetic strategy that would translate to a prototype design of an optimal identity‐preserved soya bean‐based feedstock for aquaculture, whereby a multigene stack approach for the targeted synthesis of two value‐added output traits, eicosapentaenoic acid and the ketocarotenoid, astaxanthin, were introduced into the crop. To this end, the systematic introduction of seven transgenic cassettes into soya bean, and the molecular and phenotypic evaluation of the derived novel events are described.